The impact of premature progesterone rise on the outcome of intrauterine insemination cycles with controlled ovarian hyperstimulation in unexplained infertility. (August 2016) - Mutlu, Mehmet Firat; Erdem, Mehmet; Erdem, Ahmet; Mutlu, Ilknur; Guler, Ismail; Demirdağ, Erhan
Abstract: Objective: To ascertain the incidence of premature progesterone P rise and its impact on outcomes in controlled ovarian hyperstimulation and intrauterine insemination (COH–IUI) cycles, and also to identify variables related with premature P rise. Study design: Four hundred sixty cycles of 460 couples with unexplained infertility having COH–IUI treatment with a starting dose of 75 IU recombinant FSH enrolled in this prospective study. Serum P levels were determined on the day of hCG trigger. Premature P rise was defined as progesterone ≥1 ng/mL. The primary outcome measure was live birth per cycle with regard to P levels of ≥1 ng/mL and ≥1.5 ng/mL. Secondary outcome measures were cycle characteristics associated with P rise. Results: The incidence of premature P rise was 22.0%. P levels on hCG day were significantly lower in cycles with live birth as compared to cycles without live birth 0.49 ± 0.51 vs. 0.73 ± 0.82 ng/mL. Live birth rates were significantly lower in cycles with hCG day P levels ≥1.0 ng/mL (%7.9 vs. %22.6) and ≥1.5 ng/mL (%6.4 vs. %20.8). Among age, number of dominant follicles, estradiol, LH and P levels on the day of hCG trigger, it was found that P levels was the only significant variable to predict live birth on multivariate analysis. The number of dominant follicles on hCG day and premature LH surge were the only significant variables related with premature P rise. Conclusion: Premature P is a frequent feature of COH–IUI cycles and associated with decreased live birth rates.